A Preliminary Investigation on User Factors of Phishing E-mail - Mokhtar, Ainnur Hafizah Anuar; Redzuan, Fauziah; Adnan, Wan Adilah Wan; Vincent, Rosalind J. S.; Sagir, Akhmad; Abdul-Hamid, Fazli; Abbas, Mohd Saleh (CENTRAL ASIA AND THE CAUCASUS, 2022)
The increasing rate of Internet users and the adaptation to technology are threatening security. The most prevalent threat is phishing, which uses social engineering attacks to mislead users to reveal confidential and sensitive information such as usernames and passwords. Phishing is a type of e-mail fraud in which an intruder poses a trustworthy or trusted source by clicking on a link or opening an e- mail attachment to deceive the recipient. Phishing e-mails are those that employ both social engineering and technological tricks. It is essential to use e-mails today because almost every person in the world has to use them, whether personal or business. The truth is that anyone who has used e-mails may be a possible target for cybercriminals. User factor is an essential element in a phishing e-mail. In this study, interviews were conducted to get the user factors involved in a phishing e-mail. The findings show that the user factors are demographic, behaviour, weapons of influence and e-mail contents phishing e-mail.